An analysis of the adoption patterns of fair value accounting in Zimbabwe - Juawo, Phillipa (Midlands State University, 2017)
This research undertook to examine the basic understanding of fair value accounting (FVA) in Zimbabwe and analyse the patterns within which it is adopted. The researcher’s analysis focused on the Zimbabwe Stock Exchange (ZSE), listed banks and individual Small and Medium Enterprises (SME’s). Accountants and auditors were also engaged in the research so as to determine their knowledge and their views on FVA. The researcher chose this topic because although a lot of authors have previously written about FVA, they dwell on its relevance, reliability, advantages and disadvantages and applicability to financial instruments without determining the adoption trends in their countries. Having established this gap, the researcher sought to analyse the adoption patterns of FVA in Zimbabwe. Quantitative data collection methods in the form of field surveys through a cross-sectional study of the listed banking sector, questionnaires and interviews were used in an attempt to establish the study’s objectives. Chisquare analysis was used to determine the influential variables in FVA adoption in the banking sector. The significant variables for FVA adoption in the banking sector were competitiveness and internal organizational interest. The researcher established that 41% of the sample population had adopted FVA because of their knowledge and understanding of the principle. Institutional investors are of the opinion that FVA gives them a true and faithful presentation of financial reporting in order for them to make fruitful investment decisions. SME’s and other management teams dismissed FVA as unnecessary due to high valuation costs, lack of knowledge and unreliability of measurement techniques. The researcher therefore recommended the PAAB and ICAZ to conduct training workshops for management in order to educate them on the principles of FVA.